2015
DOI: 10.5897/ajb2014.14320
|View full text |Cite
|
Sign up to set email alerts
|

Genotype x environment interaction and stability analysis for yield and yield related traits of Kabuli-type Chickpea (Cicer arietinum L.) in Ethiopia

Abstract: Chickpea is the major pulse crop cultivated in Ethiopia. However, its production is constrained due to genotype instability and environmental variability. This research was carried out to examine the magnitude of environmental effect on yield of chickpea genotypes and to investigate the stability and adaptability of genotypes under different agro-ecologies. Seventeen (17) genotypes were evaluated in randomized complete block design (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 7 publications
(7 reference statements)
8
11
0
Order By: Relevance
“…At Mata, genotype, DZ-2012-CK-20113-2-0042 was the best performer as in Alaku Belle and the performance of the local variety was the poorest in a similar fashion it displayed in Shambu and Hawa Galan (Table 4). This result is in agreement with the report of Getachew et al (2015) who showed inconsistent performances of chickpea genotypes in central and eastern Ethiopia.…”
Section: Yield Performancesupporting
confidence: 93%
“…At Mata, genotype, DZ-2012-CK-20113-2-0042 was the best performer as in Alaku Belle and the performance of the local variety was the poorest in a similar fashion it displayed in Shambu and Hawa Galan (Table 4). This result is in agreement with the report of Getachew et al (2015) who showed inconsistent performances of chickpea genotypes in central and eastern Ethiopia.…”
Section: Yield Performancesupporting
confidence: 93%
“…The AMMI stability (ASV) value is the distance from zero in a bi-plot between the IPCA 1 scores and the IPCA 2 scores (Getachew et al, 2015). In the AMMI analysis, the IPCA 1 score contributes more to the genotypeenvironment (GE) interaction sum of squares.…”
Section: Performance Of Genotypes On Grain Yieldmentioning
confidence: 99%
“…Mean, range and coefficient of variation of agronomic traits have been widely used to determine the variations available in the population. Moreover, the values of genotypic and phenotypic coefficient of variations, >20%, 10 to 20% and <10% are considered to be higher, intermediate and lower respectively (Getachew et al, 2015). The effectiveness of selection in any crop depends on the extent and nature of phenotypic and genotypic variability present in different agronomic traits found in the population (Arora, 1991;Keneni et al, 2011).…”
Section: Genotypic and Phenotypic Coefficient Of Variationmentioning
confidence: 99%
“…Rehman et al (1996) and Wahid and Ahmed (1999) reported high estimate of genetic coefficient of variability for plant height and seeds per pod. Getachew et al (2015) reported high genetic coefficients of variability for seeds per plant and seed yield per plant. High genotypic coefficient of variation indicated the availability of high genetic variation for selection and improvement; while the lower value indicated that selection is not effective for particular character because of the narrow genetic variability (Singh et al, 2003;Upadhaya et al, 2008;Mullualem et al, 2017;Shiferaw et al, 2017).…”
Section: Genotypic and Phenotypic Coefficient Of Variationmentioning
confidence: 99%